Synthesis and Characterization of a Coagulating Agent from Plantain Peel Starch (Musa paradisiaca), as Coadjuvant in Water Treatment (2023)
Coagulation processes are widely used for water treatment, mainly with chemical coagulants. In this research, starch derived from a waste (unripe plantain peel, Musa paradisiaca) was used as a starting point for a chemical modifcation. Through acetylation, its chemical structure was modifed and characterized by infrared spectrophotometry, for its evaluation as a coadjuvant in coagulation operations to reduce the turbidity of raw water. Two experimental designs were developed to evaluate the incidence of modifed starch as the main coagulant, or in conjunction with a conventional coagulant (Al2(SO4)3), at diferent (Al2(SO4)3)/acetylated starch ratios, in jar-test experiments. In the frst experimental design, with the acetylated starch as the main coagulant, turbidity removal percentages reached 47.93% (average value, 41.18%). For the (Al2(SO4)3)/acetylated starch coagulation process, 98.91% turbidity removal was reached in the second experimental design (average value, 97.16%). The impact of starch chemical substitution degree and the (Al2(SO4)3)/acetylated starch ratio on the fnal turbidity obtained in the jar-tests was determined using ANOVA test. There was a great infuence of the chemical substitution degree and the concentration of acetylated starch utilized, when modifed starch was used as the main coagulant. For the second experimental design, the (Al2(SO4)3)/acetylated starch ratio had a greater incidence on the turbidity removal. Thus, modifed starch obtained from plantain peel waste is a promising coadjuvant material for water coagulation processes.